MEASUREMENT AND INTERPRETATION OF MOLECULAR-LEVEL FORCES OF INTERACTION BETWEEN THE SIDEROPHORE AZOTOBACTIN AND MINERAL SURFACES - Kendall T.A.; Hochella M.F. (My University, 2003)
The forces of interaction were measured between the siderophore azotobactin and the minerals goethite (α-FeOOH) and diaspore (α-AlOOH) in aqueous solution using force microscopy. Azotobactin, a pyoverdin-type siderophore, was covalently linked to a hydrazide terminated atomic force microscope tip using a standard active ester protein coupling technique. Upon contact with each mineral surface, the adhesion force between azotobactin and goethite was two to three times the value observed for the isostructural Al-equivalent diaspore. The affinity for the solid iron oxide surface reflected in the force measurements correlates with the specificity of azotobactin for aqueous ferric iron. Further, the adhesion force between azotobactin and goethite significantly decreases (4 nN to 2 nN) when small amounts of soluble iron (0.1 μM FeCl3 . 6H2O) are added to the system at pH 3.5 suggesting a significant specific interaction between the chelating reactive center of azotobactin and the mineral surface. Changes in the force signature with pH and ionic strength were fairly predictable when considering mineral solubility, the charge character of the mineral surfaces, the molecular structure of azotobactin, and the intervening solution. For example, azotobactin-goethite adhesion values were consistently smaller at pH 3.5 relative to the forces at pH 7. At the lower pH, the large number of protons and the increase in the mineral solubility provides additional electron acceptors (e.g., H+ and Fe3+(aq)) that are free to compete for the basic oxygen chelating sites in the azotobactin structure. It is believed that this competition disrupts siderophore affinity for the surface resulting in decreased adhesion values.